Retinal ganglion cells adapt to ionic stress in experimental glaucoma - Boal, Andrew M.; McGrady, Nolan R.; Holden, Joseph M.; Risner, Michael L.; Calkins, David J. (Frontiers in Neuroscience, 2023)
Introduction Identification of early adaptive and maladaptive neuronal stress responses is an important step in developing targeted neuroprotective therapies for degenerative disease. In glaucoma, retinal ganglion cells (RGCs) and their axons undergo progressive degeneration resulting from stress driven by sensitivity to intraocular pressure (IOP). Despite therapies that can effectively manage IOP many patients progress to vision loss, necessitating development of neuronal-based therapies. Evidence from experimental models of glaucoma indicates that early in the disease RGCs experience altered excitability and are challenged with dysregulated potassium (K+) homeostasis. Previously we demonstrated that certain RGC types have distinct excitability profiles and thresholds for depolarization block, which are associated with sensitivity to extracellular K+. Methods Here, we used our inducible mouse model of glaucoma to investigate how RGC sensitivity to K+ changes with exposure to elevated IOP. Results In controls, conditions of increased K+ enhanced membrane depolarization, reduced action potential generation, and widened action potentials. Consistent with our previous work, 4 weeks of IOP elevation diminished RGC light-and current-evoked responses. Compared to controls, we found that IOP elevation reduced the effects of increased K+ on depolarization block threshold, with IOP-exposed cells maintaining greater excitability. Finally, IOP elevation did not alter axon initial segment dimensions, suggesting that structural plasticity alone cannot explain decreased K+ sensitivity. Discussion Thus, in response to prolonged IOP elevation RGCs undergo an adaptive process that reduces sensitivity to changes in K+ while diminishing excitability. These experiments give insight into the RGC response to IOP stress and lay the groundwork for mechanistic investigation into targets for neuroprotective therapy.